Bilingualism predicts executive function resilience after COVID-19 in aging - John G. Grundy; Melanie Pujols-Beltran (Proceedings of the National Academy of Sciences, 2026)
Bilingualism has been associated with enhanced executive functions (EFs), particularly attentional control, and may confer protection against cognitive decline in older age. At the same time, the COVID-19 pandemic has emerged as a factor negatively affecting EF in older adults. Bilingualism might offer resilience against these COVID-related cognitive declines, especially in late adulthood, by bolstering cognitive reserve. The present study collected data from 312 community-dwelling individuals spanning the adult lifespan (aged 18 to 80) to address two goals. Goal 1 was to identify a latent structure linking bilingualism and EF across the adult lifespan, using a continuous multivariate approach to help resolve controversies in the literature. Goal 2 was to determine whether bilingualism can protect against post-COVID EF decline in the most vulnerable older age group. We used partial least squares correlation (PLSC) analysis to extract latent relationships between multiple bilingual experience measures (and relevant covariates) and a battery of EF task outcomes. Results revealed that individuals with greater bilingual experience (earlier L2 age of acquisition and greater L2 proficiency) showed a multivariate association with executive function measures, with the most consistent behavioral expression observed in task-switching performance. Earlier L2 AoA was most robustly associated with better nonverbal task-switching performance among older adults reporting a history of COVID, even when modeling COVID burden continuously (i.e., number of infections and recency of last infection). These findings demonstrate that bilingual experience contributes to resilience in attentional control under flexible task-switching demands in older adults even in the context of COVID-19.